Novel glycosylation methods and their application to natural products synthesis - Toshima, K.
In this short review article, several glycosylation methods that were developed in our laboratories, including stereocontrolled glycosylation using 2,6-anhydro-2,6-dideoxy-2,6-dithio sugars for obtaining 2,6-dideoxy glycosides, C-glycosylation employing unprotected sugars, environmentally benign glycosylation utilizing heterogeneous solid acids and ionic liquids, are recounted. In addition, representative and significant applications of these methods to the synthesis of complex natural products are described.
Keywords: CARBOHYDRATE; GLYCOSYLATION; GLYCOSIDE; NATURAL PRODUCT; GLYCOMOLECULE